Fertilization Effectiveness on the Productivity of Fresh Fruit Bunches and Maintenance Costs of Oil Palm - Aji, Wandha Atmaka; Utami, Aditya Dyah; Nugroho, Bagus; Toyyibah, Toyyibah; Nurcahya, Mukti Ahmad (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2020)
The productivity of oil palm is highly dependent on the application of fertilization. Fertilizer applications must pay attention to its effectiveness and efficiency so that nutrients are absorbed optimally at the right time and right dosage. This research was conducted to assess the effectiveness of fertilization time. In addition, this also aimed to examine the effectiveness of oil palm fertilization which affects the productivity of fresh fruit bunches (FFB) and increases the production income. The data used were secondary data including fertilization and productivity of FFB at time intervals after fertilization for 6, 7, and 8 months in Kujan Estate Division, PT Menthobi Makmur Lestari (MMaL), Kujan Village, Nanga Bulik District, Lamandau, Central Kalimantan Province. The data obtained were analyzed using MS software. Excel was also employed to describe the dosage and time applied for 1 year and the productivity of FFB after 6 months of fertilization. Fertilizer application in months with high rainfall and long dry season is less effective and efficient for nutrient availability. The productivity of FFB in the second semester after 6 months of fertilization has increased compared to the first semester. The effective application of fertilizers can increase the production of CPO and reduce the total maintenance cost of the oil palm company